Dynamical and spectral properties of some double clusters in the LMC. - Kontizas, M.; Chrysovergis, M.; Kontizas, E.; Hatzidimitriou, D. (1989)
The dynamical properties and stellar content of some cluster pairs in the LMC were studied, using UKST plates. Positive evidence was found for significant distortions in the density profiles of the clusters, particularly in the outer regions. These disturbances were interpreted as indications of dynamical interaction between the pair members. Some of the pairs were found to have very similar stellar content, and ages ranging from a few 107yr to several 108yr.
Keywords: Astronomical Photometry; Astrophysics; binary stars; Galactic Structure; Gravitational Effects; Magellanic Clouds; Magellanic Clouds: Star Clusters; Spectrum Analysis; star clusters; Star Clusters: Dynamics; Star Clusters: Stellar Content; stellar evolution; Stellar Motions